Expression and Localization of Connexins in the Outer Retina of the Mouse - Bolte, Petra; Herrling, Regina; Dorgau, Birthe; Schultz, Konrad; Feigenspan, Andreas; Weiler, Reto; Dedek, Karin; Janssen-Bienhold, Ulrike (Journal of Molecular Neuroscience, 2016)
The identification of the proteins that make up the gap junction channels between rods and cones is of crucial importance to understand the functional role of photoreceptor coupling within the retinal network. In vertebrates, connexin proteins constitute the structural components of gap junction channels. Connexin36 is known to be expressed in cones whereas extensive investigations have failed to identify the corresponding connexin expressed in rods. Using immunoelectron microscopy, we demonstrate that connexin36 (Cx36) is present in gap junctions of cone but not rod photo-receptors in the mouse retina. To identify the rod connexin, we used nested reverse transcriptase polymerase chain reaction and tested retina and photoreceptor samples for messenger RNA ( mRNA) expression of all known connexin genes. In addition to connexin36, we detected transcripts for connexin32, connexin43, connexin45, connexin50, and connexin57 in photoreceptor samples. Immunohistochemistry showed that connexin43, connexin45, connexin50, and connexin57 proteins are expressed in the outer plexiform layer. However, none of these connexins was detected at gap junctions between rods and cones as a counterpart of connexin36. Therefore, the sought-after rod protein must be either an unknown connexin sequence, a connexin36 splice product not detected by our antibodies, or a protein from a further gap junction protein family.
Keywords: Connexin; Electrical synapse; Gap junction; Photoreceptor; Retina; Rod-cone coupling